2020
DOI: 10.18203/issn.2454-2156.intjscirep20201268
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of maternal near miss in selected health facilities of Berak Woreda, Oromia national regional state, Ethiopia

Abstract: <p class="abstract"><strong>Background:</strong> Maternal near miss is one of the related concepts to maternal mortality where women survive merely by chance, luck, or by good hospital care. The present study was aimed to fill the prevailing knowledge gap on maternal near miss ratio and events and identify factors associated with near miss in selected health facilities of berak woreda. To determine associated factors of maternal near miss in selected health facilities of Berak woreda, Oromia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Both studies were carried out in Tertiary hospitals in Nigeria, which may explain the similarities. In contrast, polygamy, rural housing, long distance from hospital, poor monthly income, and job in the agricultural sector were identified as significant associations in research conducted in Uganda, Ethiopia, South Sudan, and India [9,15,17,19,21,23]. .2 γ = number of pregnancies was not stated in some folders Single marital status was observed to be the most significant socio-demographic predictor of maternal near miss, with a two-fold increase in risk when compared to married counterparts.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Both studies were carried out in Tertiary hospitals in Nigeria, which may explain the similarities. In contrast, polygamy, rural housing, long distance from hospital, poor monthly income, and job in the agricultural sector were identified as significant associations in research conducted in Uganda, Ethiopia, South Sudan, and India [9,15,17,19,21,23]. .2 γ = number of pregnancies was not stated in some folders Single marital status was observed to be the most significant socio-demographic predictor of maternal near miss, with a two-fold increase in risk when compared to married counterparts.…”
Section: Discussionmentioning
confidence: 82%
“…Maternal mortality has been shown to be a small fraction of the burden of maternal morbidity, as it represents only the end of a spectrum, hence the need to evaluate maternal near miss [1,2,12,24]. Maternal "near-miss obstetrics events" (MNM) is a review of cases at the severe end of the maternal morbidity spectrum of women who nearly died but survived a life-threatening condition during pregnancy, delivery and postpartum [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal near-miss due to obstructed labor. Seven studies reported the prevalence of maternal near-miss due to OL and the pooled prevalence of maternal near-miss was estimated to be 30.5% [30.5 (11.40, 49.59), I 2 = 99.3%, p < 0.001] (Fig 3) [40][41][42][67][68][69][70]]. Egger's test showed a non-significant publication bias, (p-value > 0.830).…”
Section: Plos Onementioning
confidence: 99%